APPLICATION OF ACTIVITY BASED COSTING TO INCREASE COMPANY PROFITABILITY - Febri, Wanda; Yusrinaldi, Yusrinaldi Rahman Margolang; Zinedine, Zahara (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to determine the application of Activity Based Costing in increasing the company's profitability. In this study using data collection methods with document data or archives carried out by examining documents related to research interests, namely. library research. The results of this study indicate that the traditional approach to the Activity Based Costing approach is able to increase the company's profitability. The difference that occurs is due to the imposition of overhead costs on each product. In the traditional method, the overhead costs for each product are only charged to one cost driver, namely the number of production units. In the Activity based costing system, overhead costs for each product are charged to several cost drivers so that the activity based costing system is able to allocate activity costs to each product appropriately based on the consumption of each activity.